2002
DOI: 10.1093/alcalc/37.4.362
|View full text |Cite
|
Sign up to set email alerts
|

The Readiness to Change Questionnaire in Subjects With Hazardous Alcohol Consumption, Alcohol Misuse and Dependence in a General Population Survey

Abstract: Classification did not differ substantially according to the method of allocation. A three-factor solution, as reported in the literature, could not be replicated. Allocation to stages of change with the RCQ reflected predictions made from the Transtheoretical Model of behaviour change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 42 publications
1
28
1
1
Order By: Relevance
“…The results of the Lithuanian version of the RCQ indicate that Cronbach's alpha coefficients are acceptable for group testing. The internal consistency of readiness to change alcohol consumption action stage is similar comparing to the original RCQ data (Rollnick et al, 1992) and to those found in other studies of the RCQ validation for other cultures (Defuentes-Merillas et al, 2002;Hannover et al, 2002;Forsberg et al, 2003). Furthermore, the internal consistency of readiness to change alcohol consumption precontemplation and contemplation stages and of readiness to change smoking, physical activity and diet stages are lower comparing to other studies (Defuentes-Merillas et al, 2002;Hannover et al, 2002;Pullen & Walker, 2002;Forsberg et al, 2003;Degen et al, 2014;Kheawwan et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The results of the Lithuanian version of the RCQ indicate that Cronbach's alpha coefficients are acceptable for group testing. The internal consistency of readiness to change alcohol consumption action stage is similar comparing to the original RCQ data (Rollnick et al, 1992) and to those found in other studies of the RCQ validation for other cultures (Defuentes-Merillas et al, 2002;Hannover et al, 2002;Forsberg et al, 2003). Furthermore, the internal consistency of readiness to change alcohol consumption precontemplation and contemplation stages and of readiness to change smoking, physical activity and diet stages are lower comparing to other studies (Defuentes-Merillas et al, 2002;Hannover et al, 2002;Pullen & Walker, 2002;Forsberg et al, 2003;Degen et al, 2014;Kheawwan et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…Thus, although the targets of behavioral change differ, the structure of the change process appears to be the same (Miller & Rollnick, 2002) and researchers have found that the original three-factor solution describes data the best (Defuentes-Merillas et al, 2002;Forsberg et al, 2003;Forsberg et al, 2004;Heather & Honekopp, 2008;Ouimet et al, 2010). On the other hand, some studies have failed to replicate original factor solution proposed by Rollnick et al (1992) (Bombardier & Heinemann, 2000;Rodriguez-Martos et al, 2000;Hannover et al, 2002;Nielson et al, 2003;Kheawwan et al, 2016).…”
Section: Readiness To Change Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…The stages of change were assessed using a German translation of the Readiness to Change Questionnaire[23,24,25,26]. Stages of change were allocated by using the quick method [23].…”
Section: Methodsmentioning
confidence: 99%
“…It was specifically developed for use in brief opportunistic interventions among excessive drinkers and has been studied in at least five countries, in as many different languages and cultures, but among a more limited range of subjects (Defuentes-Merillas, Dejong, & Schippers, 2002;Forsberg, Halldin, & Wennberg, 2003;Hannover et al, 2002;Rodriguez-Martos et al, 2000). Findings have been almost as diverse, with some since questioning the threestage model and instead advocating for either a continuous (Budd & Rollnick, 1996) or a two-stage alternative (precontemplation and contemplation/action; Willoughby & Edens, 1996).…”
Section: Introductionmentioning
confidence: 99%